Does the local government multi-objective competition intensify the transfer of polluting industries in the Yangtze River Economic Belt? - Ding, Xuhui; Liu, Huihui; Zhang, Jiatong; Shen, Yicong; Yang, Guang (Environmental research, 2024)
Exploring the effect of local government multi-objective competition on the transfer of polluting industries is of great practical significance for promoting the high-quality development in the Yangtze River Economic Belt. This paper adopted the extended shift-share analysis method to measure the scale of inter-provincial transfer of polluting industries in the Yangtze River Economic Belt from 2008 to 2020. Considering local governments' economic, innovation, talent and environmental protection competition, the paper examined the effects of local government multi-objective competition on the transfer of polluting industries in the region, and tested its spatial spillover effects. The results showed that: 1. Different competitions had different effects on the transfer of polluting industries. Economic competition intensified the transfer of polluting industries, while talent, innovation, and environmental protection competition all restrained it, among which environmental protection competition had the strongest restraining effect. 2. Compared with the transfer of polluting industries, the direction of economic competition and environmental protection competition on the transfer of industries did not change, but the degree of influence was reduced, talent competition instead promoted industrial transfer of the research region to some extent. 3. From the basin level, government competition in the upstream region more obviously intensified the transfer of polluting industries; while from the economic scale level, the restraining effect of government competition in the developed region on the transfer of polluting industries was much stronger. 4. Both innovation and environmental protection competition had positive spatial spillover effects. Therefore, it is necessary to optimize the promotion and assessment mechanism of local officials, adopt differentiated competitive constraint mechanisms in accordance with local conditions, guide local governments to transform their development concepts, promote the sharing and common use of technological innovations, and promote the orderly transfer of industries in the Yangtze River Economic Belt. •Government economic competition intensified the transfer of polluting industries.•Talent, innovation, and environmental protection competition had restraining effect.•Environmental protection competition had the strongest restraining effect.•The impact of government competition had regional and scale heterogeneity.•Innovation and environmental protection competition had spatial spillover effect.